Composite membrane based on two-dimensional covalent organic framework as well as preparation method and application of composite membrane
By doping carbon nanotubes in the COF membrane and preparing a two-dimensional covalent organic frame composite membrane using ultrasonic dissolution and vacuum pressurization assembly technology, the problem of pore size mismatch in the COF membrane is solved, and efficient separation performance and stable performance maintenance are achieved.
Patent Information
- Application Number
- CN202411897026.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The pore size of the existing COF membrane materials is larger than the kinetic diameter of the target molecule and the preparation method is complex, which limits its application in the field of separation.
A covalent organic frame was formed with a composite film with carbon nanotubes by reacting 2,4,6-triformyl phthalglucoside and 2,5-diaminobenzenesulfonic acid ligand. A two-dimensional covalent organic frame composite film with excellent separation performance was prepared by ultrasonic dissolution and vacuum pressurization assembly technology.
It achieves high interception and good anti-fouling performance, is suitable for seawater desalination and dye separation, and has a high performance retention rate, far exceeding some current seawater desalination membranes.
Smart Images

Figure CN119701656A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of membrane materials, and in particular to a two-dimensional covalent organic framework-based composite membrane and a preparation method and application thereof. Background Art
[0002] The traditional chemical separation and purification process consumes a huge amount of energy, which puts great pressure on environmental protection and the rational use of energy. In contrast, the membrane separation process is expected to become a new generation of separation technology due to its advantages such as high efficiency, low energy consumption and economic feasibility. The improvement of membrane separation performance lies in the selection and development of membrane materials. Covalent organic framework materials are a new type of crystalline porous organic skeleton materials. The periodic pore structure and functional adjustability make them have great application potential in membrane separation fields such as gas separation, water treatment, and organic solvent nanofiltration. However, the pore size of the COF materials reported so far is generally larger than the kinetic diameter of the target molecule, and the method for preparing COF membranes with good separation performance is not very mature, which greatly limits the application of COF membranes. Therefore, it is extremely important to prepare COF membrane materials with excellent separation performance and good stability through the rational design of the building unit and the effective development of the membrane preparation method. The composite membrane prepared in the present invention is doped with carbon nanotubes, whose high specific strength, strong flexibility, good conductivity and chemical stability can improve the performance of the separation membrane, and the substituents on the carbon nanotubes, such as hydroxyl groups, can also interact with the ions to be measured to achieve the purpose of separation.
[0003] CN118745264A discloses a covalent organic framework membrane and its preparation method and application. The patent application does not explore the separation application, and the synthesis steps are complicated. The hydrothermal method and freeze drying in the synthesis process are more expensive and the process is more complicated. CN112973468A discloses a method for preparing a two-dimensional covalent organic framework ultra-thin nanosheet material composite membrane and its application. The film manufacturing process in the patent application requires dipping and coating, and it is difficult to achieve uniform film thickness.
[0004] In summary, the research on new preparation process based on two-dimensional covalent organic framework composite membranes is of great value. Summary of the invention
[0005] In view of this, the present invention proposes a two-dimensional covalent organic framework composite membrane and a preparation method and application thereof.
[0006] The present invention specifically relates to a covalent organic framework composite membrane and its preparation and application in seawater desalination. The covalent organic framework composite membrane is assembled from a covalent organic framework material (COF), a carbon nanotube (CNT) and a nylon membrane. The composite membrane prepared in the present invention is doped with carbon nanotubes, which have high specific strength, strong flexibility, good electrical conductivity and chemical stability and can improve the performance of the separation membrane. Substituents on the carbon nanotubes, such as hydroxyl groups, can also interact with ions to be measured to achieve the purpose of separation.
[0007] The technical solution of the present invention is achieved in this way:
[0008] A method for preparing a two-dimensional covalent organic framework composite membrane comprises the following steps:
[0009] Step 1, ultrasonically dissolving 2,4,6-triformylphloroglucinol in dichloromethane to obtain a 2,4,6-triformylphloroglucinol solution; ultrasonically dissolving a diamine monomer 2,5-diaminobenzenesulfonic acid in deionized water to obtain a diamine monomer 2,5-diaminobenzenesulfonic acid solution; pouring the 2,4,6-triformylphloroglucinol solution into the bottom layer of a container, slowly dripping deionized water as a buffer, and dripping the diamine monomer 2,5-diaminobenzenesulfonic acid solution on the top layer; under static conditions, performing a synthesis reaction at room temperature; after the reaction is completed, using a pipette to suck out the upper layer of nanosheets and put them into a treated dialysis bag; dialyzing the synthesized nanosheets in deionized water to obtain TpPa-SO3H nanosheets, that is, a covalent organic framework nanosheet solution;
[0010] Step 2, taking carbon nanotubes, adding an organic solvent, and dissolving by ultrasonication to obtain a carbon nanotube solution;
[0011] Step 3, taking the carbon nanotube solution prepared in step 2, mixing it with the covalent organic framework nanosheet solution by ultrasonication, assembling it on a nylon membrane by vacuum pressure, and drying it to obtain a two-dimensional covalent organic framework composite membrane.
[0012] Furthermore, in step 1, the molar ratio of the 2,4,6-triformylphloroglucinol to the diamine monomer 2,5-diaminobenzenesulfonic acid is 1:1.4-1.6;
[0013] The molar volume of the 2,4,6-triformylphloroglucinol and dichloromethane is 0.075mmol:90-120mL;
[0014] The molar volume of the diamine monomer 2,5-diaminobenzenesulfonic acid and deionized water in the diamine monomer 2,5-diaminobenzenesulfonic acid solution is 0.112mmol:90-120mL;
[0015] The volume ratio of the 2,4,6-triformylphloroglucinol solution to the buffer solution is 90-110 ml:60 ml.
[0016] Furthermore, in step 1, the ultrasonication time is 30-40 minutes.
[0017] Furthermore, in step 1, the synthesis reaction time is 60-90h.
[0018] Furthermore, in step 1, the dialysis treatment time is 60-90 hours.
[0019] Furthermore, in step 2, the solid-liquid ratio of the carbon nanotubes to the organic solvent is 1 mg:10-15 ml.
[0020] Furthermore, in step 2, the carbon nanotubes are at least one of hydroxyl carbon nanotubes, amino multi-walled carbon nanotubes, and multi-walled carbon nanotubes; and the organic solvent is at least one of acetonitrile and N,N-dimethylformamide.
[0021] Furthermore, in step 3, the mass volumes of the carbon nanotube solution and the covalent organic framework nanosheets are 2 ml:10-15 ml.
[0022] A two-dimensional covalent organic framework-based composite membrane is prepared by any preparation method described in the present invention.
[0023] The two-dimensional covalent organic framework-based composite membrane of the present invention is used in seawater desalination or dye separation.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1) The present invention uses 2,4,6-triformylphloroglucinol and 2,5-diaminobenzenesulfonic acid ligands to react to form a covalent organic framework and carbon nanotubes to form a composite membrane with anionic sulfonate groups. The membrane material has abundant charged points. Due to the electrostatic repulsion between the membrane surface and the solute, it often has a higher retention rate and good antifouling performance for solutes with the same negative charge as the composite membrane. It can be applied to the fields of seawater desalination, dye separation, etc.
[0026] (2) Compared with the undoped pure COF membrane, the composite membrane prepared in the present invention is doped with carbon nanotubes, whose high specific strength, strong flexibility, good conductivity and chemical stability can improve the performance of the separation membrane, and the substituents on the carbon nanotubes, such as hydroxyl groups, will also interact with the ions to be measured to achieve the purpose of separation. Covalent organic framework composite membranes are applied in the field of salt separation and show significantly improved salt rejection and permeation flux. Even after dozens of tests, its performance retention rate is high, far exceeding some current seawater desalination membranes, and thus has great application prospects in the separation field.
[0027] (3) The two-dimensional covalent organic framework composite membrane adopts a two-step synthesis process, and the preparation method is simple, which is conducive to large-scale manufacturing. At the same time, the raw material cost is low and it has the characteristics of environmental friendliness. In addition, the covalent organic framework material prepared by the Schiff base reaction is further assembled into a composite membrane with the advantage of recycling. It can be dissolved in an acidic solution and does not pollute the environment.
[0028] (4) Compared with the CN118745264A (abbreviated as D1) process, the differences from D1 include: the synthesis process of the two is different. D1 uses hydrothermal reaction to generate a composite with graphene, and then is modified by gold nanoparticles. The present invention uses a two-phase method to generate a nanosheet solution, which is mixed with carbon nanotubes and then filtered and assembled; the substances doped in the composite membranes of the two are different. The present invention uses carbon nanotubes, and D1 includes graphene and gold nanoparticles; the application fields of the two are different. The membrane of D1 is suitable for the detection of substances such as formaldehyde and benzaldehyde, and the membrane of the present invention is suitable for the separation and interception of salt components in seawater. Compared with the D1 process, the synthesis steps of the present invention are simple, and the types of materials used are small; and the conditions required for synthesis are relatively mild, and do not need to be heated to 120°C. The present invention directly generates COF material nanosheets at room temperature, and the nanosheets are more conducive to the stacking between layers to form a tightly arranged thin film; the conditions for forming the nanosheets are mild, the steps are simple, and no additional environmental requirements are added; and the composite film does not need to add graphene, sodium hydroxide, gold particles and other substances, but only needs to be doped with a small amount of carbon nanotubes.
[0029] (4) Compared with the CN112973468A (abbreviated as D2) process, the monomers used in the two are different, and the present invention does not use 2,6-diaminoanthraquinone; the main bodies of the films of the two are different, the main substrate of the D2 film is carbon nanotubes, and the film substrate of the present invention is nylon film, and carbon nanotubes only act as a small amount of doping substances to affect the properties of the film; the application fields of the two are different, the D2 film is used for supercapacitors, and the present invention is used for salt solution separation. Secondly, the film manufacturing process in D2 requires dipping and coating, and it is difficult to achieve uniform film thickness. The assembly of the composite film of the present invention only requires vacuum pump filtration, and does not require dipping and coating to achieve uniform film thickness. Pressurization during the filtration process can achieve uniform film thickness. Moreover, the present invention does not require grinding when synthesizing COF materials, and only requires spontaneous reaction at room temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Schematic diagram of the covalent organic framework nanosheet structure;
[0031] Figure 2 Optical photograph of covalent organic framework nanosheet solution;
[0032] Figure 3 Particle size diagram of covalent organic framework nanosheet solution;
[0033] Figure 4 Zeta potential diagram of covalent organic framework nanosheet solution;
[0034] Figure 5 XRD pattern of covalent organic framework powder prepared by solvothermal method;
[0035] Figure 6 Physical picture of covalent organic framework film (undoped CNT);
[0036] Figure 7 XRD comparison of covalent organic framework film (undoped CNT), nylon substrate, and powder;
[0037] Figure 8 The relationship between the volume of added nanosheets and the salt rejection and flux;
[0038] Fig. 9 The relationship between the volume of added hydroxyl carbon nanotubes and the salt rejection rate and flux;
[0039] Fig.10 The relationship between the type of carbon nanotubes added and the salt rejection rate and flux. DETAILED DESCRIPTION
[0040] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.
[0041] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.
[0042] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.
[0043] Table 1 Chinese meaning
[0044] Serial number English or abbreviation Chinese 1 Tp 2,4,6-Triformylphloroglucinol 2 COF Covalent organic framework materials 3 CNT Carbon Nanotubes 4 <![CDATA[Pa-SO3H]]> Diamine monomer 2,5-diaminobenzenesulfonic acid 5 DMF N,N-Dimethylformamide
[0045] Embodiment 1
[0046] Preparation of covalent organic framework composite membranes:
[0047] Step 1, prepare the covalent organic framework nanosheet solution: ultrasonically dissolve 0.075mmol 2,4,6-triformylphloroglucinol (Tp) in 100mL dichloromethane (DCM) for 30min, ultrasonically dissolve 0.112mmol diamine monomer 2,5-diaminobenzenesulfonic acid (Pa-SO3H) in 100mL deionized water for 30min, pour the Tp solution into the bottom of the beaker, slowly add 60ml of deionized water as a buffer, and drop the diamine solution on the top layer. Under static conditions, synthesize at room temperature for 3 days. After the reaction is completed, use a pipette to suck out the upper nanosheets and put them into the treated dialysis bag. The synthesized nanosheets are dialyzed in deionized water for 3 days to completely remove the residual diamine monomers to obtain red TpPa-SO3H nanosheets. The structure and physical objects are as follows Figure 1 , Figure 2 As shown; the particle size and Zeta potential were tested. Figure 3 , Figure 4 As shown; To characterize the nanosheets, they were assembled on a nylon substrate by filtration and subjected to XRD testing, as shown Figure 6 , Figure 7 shown.
[0048] Step 2, preparing carbon nanotube solution:
[0049] (1) Weigh 1 mg of hydroxy carbon nanotubes, add 10 ml of acetonitrile, and dissolve by ultrasonication (30 min) to obtain a hydroxy carbon nanotube solution;
[0050] (2) Weighing 1 mg of amino-modified multi-walled carbon nanotubes, adding 10 ml of N,N-dimethylformamide (DMF), and dissolving by ultrasonication (30 min) to obtain an amino-modified multi-walled carbon nanotube solution;
[0051] (3) Weigh 1 mg of multi-walled carbon nanotubes, add 10 ml of acetonitrile, and dissolve by ultrasonication (30 min) to obtain a multi-walled carbon nanotube solution.
[0052] Step 3, preparing a covalent organic framework composite membrane: taking 2 ml of the prepared carbon nanotube solution, mixing it with 10 ml of the covalent organic framework nanosheets by ultrasonic homogeneity (30 min), assembling it on a nylon membrane by vacuum pressure, and storing it dry at room temperature.
[0053] The relationship between the volume of nanosheets added to the covalent organic framework composite membrane and the salt rejection rate and flux was tested using a cross-flow filtration flat membrane tester. Figure 8As shown. The left side shows the salt rejection rate of the covalent organic framework composite membrane for 1mM Na2SO4 solution, and the right side shows the permeation flux of 1mM Na2SO4 solution. 2mL, 4mL, 6mL, 8mL and 10mL of nanosheet solution were taken for vacuum pressurization and assembled into membranes for testing. As the volume of the nanosheets increases, the salt rejection rate of the film gradually increases and the permeation flux gradually decreases. The test pressure is 0.60MPa, the temperature is 23℃, and the effective test area is 0.9cm 2 The calculation formula is:
[0054]
[0055]
[0056] The relationship between the volume of hydroxyl carbon nanotubes added to the covalent organic framework composite membrane and the salt rejection rate and flux was tested using a cross-flow filtration flat membrane tester. Fig. 9 As shown. The left side shows the salt rejection rate of the covalent organic framework composite membrane for 1mM Na2SO4 solution, and the right side shows the permeation flux of 1mM Na2SO4 solution. 0mL, 1m, 2mL and 3mL of hydroxy carbon nanotube solution and 10mL of nanosheets were vacuum pressurized to assemble into membranes and tested at a test pressure of 0.60MPa and a temperature of 23℃.
[0057] The relationship between the type of carbon nanotubes added to the covalent organic framework composite membrane and the salt rejection rate and flux was tested using a cross-flow filtration flat membrane tester. Fig.10 As shown. The left side shows the salt rejection rate of the covalent organic framework composite membrane for 1mM Na2SO4 solution, and the right side shows the permeation flux of 1mM Na2SO4 solution. 2mL of hydroxyl carbon nanotubes, amino carbon nanotubes, and unsubstituted multi-walled carbon nanotube solutions were taken and 10mL of nanosheets were vacuum-pressurized to assemble into membranes for testing. The test pressure was 0.60MPa and the temperature was 23℃.
[0058] Compared with the undoped pure COF membrane, the composite membrane prepared in the present invention is doped with carbon nanotubes, whose high specific strength, strong flexibility, good conductivity and chemical stability can improve the performance of the separation membrane, and the substituents on the carbon nanotubes, such as hydroxyl groups, will also interact with the ions to be measured to achieve the purpose of separation. Covalent organic framework composite membranes are applied in the field of salt separation and show significantly improved salt rejection and permeation flux. Even after dozens of tests, its performance retention rate is high, far exceeding some current seawater desalination membranes, and thus has great application prospects in the field of separation.
[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a two-dimensional covalent organic framework composite membrane, characterized in that: The following steps are involved: Step 1, ultrasonically dissolving 2,4,6-triformylphloroglucinol in dichloromethane to obtain a 2,4,6-triformylphloroglucinol solution; ultrasonically dissolving a diamine monomer 2,5-diaminobenzenesulfonic acid in deionized water to obtain a diamine monomer 2,5-diaminobenzenesulfonic acid solution; pouring the 2,4,6-triformylphloroglucinol solution into the bottom layer of a container, slowly dripping deionized water as a buffer, and dripping the diamine monomer 2,5-diaminobenzenesulfonic acid solution on the top layer; under static conditions, performing a synthesis reaction at room temperature; after the reaction is completed, using a pipette to suck out the upper layer of nanosheets and put them into a treated dialysis bag; dialyzing the synthesized nanosheets in deionized water to obtain TpPa-SO3H nanosheets, that is, a covalent organic framework nanosheet solution; Step 2, taking carbon nanotubes, adding an organic solvent, and dissolving by ultrasonication to obtain a carbon nanotube solution; Step 3, taking the carbon nanotube solution prepared in step 2, mixing it with the covalent organic framework nanosheet solution by ultrasonication, assembling it on a nylon membrane by vacuum pressure, and drying it to obtain a two-dimensional covalent organic framework composite membrane.
2. The method for preparing a two-dimensional covalent organic framework composite membrane according to claim 1, characterized in that: In step 1, the molar ratio of the 2,4,6-triformylphloroglucinol to the diamine monomer 2,5-diaminobenzenesulfonic acid is 1:1.4-1.6; The molar volume of the 2,4,6-triformylphloroglucinol and dichloromethane is 0.075mmol:90-120mL; The molar volume of the diamine monomer 2,5-diaminobenzenesulfonic acid and deionized water in the diamine monomer 2,5-diaminobenzenesulfonic acid solution is 0.112mmol:90-120mL; The volume ratio of the 2,4,6-triformylphloroglucinol solution to the buffer solution is 90-110 ml:60 ml.
3. The method for preparing a two-dimensional covalent organic framework composite membrane according to claim 1, characterized in that: In steps 1 to 3, the ultrasonication time is 30-40 minutes.
4. The method for preparing a two-dimensional covalent organic framework composite membrane according to claim 1, characterized in that: In step 1, the synthesis reaction time is 60-90h.
5. The method for preparing a two-dimensional covalent organic framework composite membrane according to claim 1, characterized in that: In step 1, the dialysis treatment time is 60-90 hours.
6. The method for preparing a two-dimensional covalent organic framework composite membrane according to claim 1, characterized in that: In step 2, the solid-liquid ratio of the carbon nanotubes to the organic solvent is 1 mg:10-15 ml.
7. The method for preparing a two-dimensional covalent organic framework composite membrane according to claim 1, characterized in that: In step 2, the carbon nanotubes are at least one of hydroxyl carbon nanotubes, amino multi-walled carbon nanotubes, and multi-walled carbon nanotubes; and the organic solvent is at least one of acetonitrile and N,N-dimethylformamide.
8. The method for preparing a two-dimensional covalent organic framework composite membrane according to claim 1, characterized in that: In step 3, the mass volumes of the carbon nanotube solution and the covalent organic framework nanosheets are 2 ml:10-15 ml.
9. A two-dimensional covalent organic framework composite membrane, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the two-dimensional covalent organic framework composite membrane according to claim 9 in seawater desalination or dye separation.
Citation Information
Patent Citations
Two-dimensional oximidation covalent organic framework electrode membrane and preparation method and application thereof
CN114887492A
Ligand, covalent organic framework material, SWCNT / COF-ET59 composite film and application
CN115286516A
Nanofiltration membrane as well as preparation method and application thereof
CN117160248A
Preparation of COF / MXene membrane with mixed dimension pore channels and application of COF / MXene membrane in water treatment
CN117753228A
Cited By
Method for synthesizing ionic covalent organic framework nanosheet in mild water phase and application of nanosheet
CN121005849A
Method for the mild aqueous phase synthesis of ionic covalent organic framework nanosheets and applications of the nanosheets
CN121005849B